Prevalence of Sleep Disordered Breathing in a Population of Canadian Grainworkers - Sean P Keenan; Kathleen A Ferguson; Moira Chan-Yeung; John A Fleetham (Canadian Respiratory Journal)
OBJECTIVES: To determine the prevalence of sleep disordered breathing (SDB) in a Canadian population of industrial workers (grainworkers). To determine the clinical features that are predictive of SDB and the validity of self-reported snoring.